HOIL-1-catalysed ubiquitylation of unbranched glucosaccharides and its activation by ubiquitin oligomers - Kelsall,IR; McCrory,EH; Xu,Y; Scudamore,CL; Nanda,SK; Mancebo-Gamella,P; Wood,NT; Knebel,A; Matthews,SJ; Cohen,P (2021)
Abstract HOIL-1, a component of the Linear Ubiquitin Assembly Complex (LUBAC), ubiquitylates serine and threonine residues in proteins, forming ester bonds (Kelsall et al, 2019, PNAS 116, 13293-13298). Here we report that mice expressing the E3 ligase-inactive HOIL-1[C458S] mutant accumulate polyglucosan in brain, cardiac muscle and other organs, indicating that HOIL-1’s E3 ligase activity is essential to prevent these toxic polysaccharide deposits from accumulating. We found that HOIL-1 monoubiquitylates glycogen and α1:4-linked maltoheptaose in vitro and identify the C6 hydroxyl moiety of glucose as the site of ester-linked ubiquitylation. The HOIL-1-catalysed monoubiquitylation of maltoheptaose was accelerated >100-fold by Met1-linked or Lys63-linked ubiquitin oligomers, which interact with the catalytic RBR domain of HOIL-1. HOIL-1 also transferred preformed ubiquitin oligomers to maltoheptaose en bloc , producing polyubiquitylated maltoheptaose in one catalytic step. The Sharpin and HOIP components of LUBAC, but not HOIL-1, bound to amylose resin in vitro , suggesting a potential function in targeting HOIL-1 to unbranched glucosaccharides in cells. We suggest that monoubiquitylation of unbranched glucosaccharides may initiate their removal by glycophagy to prevent precipitation as polyglucosan.